Поиск Google ничего не нашел

f(x)=-x^2-2x-1 - solution

www.geteasysolution.com

Simple and best practice solution for f(x)=-x^2-2x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

What is the instantaneous rate of change... | Yahoo Answers

answers.yahoo.com

Updated: If you are saying (x)=(x^2 - 2)/(x-1) [please update your equation with brackets and powers if this is incorrect] to determine the instantaneous rate of change, we need to calculate the derivative, and then substitute our value of x=2 to obtain the instantantaneous rate of change.

SOLUTION: For the function f(x)=x^2-2x+1 (a) find f(0) (b) solve f(x)=0

www.algebra.com

Question 124256This question is from textbook Structure and Method Book 1 : For the function f(x)=x^2-2x+1 (a)find f(0) (b)solve f(x)=0 This question is from textbook Structure and Method Book 1. Answer by MathLover1(12345) (Show Source)

1. Simplify x(3x+2) - (2x-4) 2. f(x)= (x+2) (2x-1) Evaluate... | eNotes

www.enotes.com

Calculate the price she paid for the painting. 5. Solve the simultaneous equation: 3x= 7y 12y= 5x-1' and find homework help for other Math questions at eNotes.

f(x) = x^2 +2x+1, root - Wolfram|Alpha Results

m.wolframalpha.com

Related Links » Give us feedback ».

Find all polynomials $p$ such that $p(x+1)=p(x)+2x+1.$

math.stackexchange.com

Find all polynomials $p$ such that $p(x+1)=p(x)+2x+1.$ I obtained $p(1)=p(-1).$ I claimed that $p(x)=x^2$ but was unable to prove it. Any help will be appreciated.

10.3.1. Уравнение касательной.

www.mathematics-repetition.com

Находим значение данной функции в точке х=1, получаем: f (x0)=f (1) = 1. Найдем производную данной функции по формуле производной степени

Function Notation: Introduction / Evaluating at a Number

www.purplemath.com

For functions, the two notations mean the exact same thing, but "f(x)" gives you more flexibility and more information. You used to say "y = 2x + 3; solve for y when x = –1". Now you say "f(x) = 2x + 3; find f(–1)" (pronounced as "f-of-x is 2x plus three; find f-of-negative-one").

algebra precalculus - Let $(f \circ g)(x) = x^2 +2x -1$. Find...

math.stackexchange.com

is there a more general way to solve this sort of problem? You've manipulated $x^2 + 2x-1$ into a form that is meaningful to $f(x+2)$, but it seems like you've done it in a sort of trial-and-error way (a heuristic way).

Поиск реализован с помощью Yandex XML и Google Custom Search API